Evaluation of the bonding quality of E. grandis cross-laminated timber made with a one-component polyurethane adhesive - Dugmore, Michael Keith (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFor)--Stellenbosch University, 2018.